Factors affecting employee job performance: a study in Majlis Bandaraya Shah Alam (MBSA) / Fidzarul Asyraf Mohd Fadzil - Mohd Fadzil, Fidzarul Asyraf (Faculty of Business and Management, 2015)
Employees are the key factors that determine the successful of a business in an organization. As such, how to sustain the morale of these employees to be more committed towards their job is in fact, a challenging task for the top management to ensure that their subordinates are satisfied with the overall benefits that the organization offer which is in this case is salary, reward and working environment. Thus, the purpose of this study is to investigate on how employee job performance can be simultaneously boosts and enhanced through supporting factors mentioned earlier. The research question is do these factors have the capabilities to contribute towards worker job performance? Is there a strong positive relationship between these variables towards employee job performance? This study is carried out in Majlis Bandaraya Shah Alam (MBSA). In particular, this research concentrates on the factors affecting employee job performance in a setting of the mentioned company. During the process of the research, A self-administered questionnaire survey collected 50 respondents, who are the employees of the respective company. The results of the descriptive analysis revealed the importance of a sufficient salary, reward system and comfortable working environment give by the organization in exchange for employee’s morale and commitment in increasing job performance. The findings of the study also highlighted that study should be conducted to other public sector setting so that the results can be generalize to entire Malaysia employees that work in the public sector.